Health Risk Assessment Via the Consumption of Clam (Corbicula largillierti) Accumulated Heavy Metals (Pb) and Coliform Bacteria at Kapuas River, West Borneo - Widya Rahayu; Dahlia Wulan Sari (Journal of Aquaculture and Fish Health, 2023)
As population activity is increasing and the Kapuas river is still a means of transportation, causing Corbicula largillierti to accumulate heavy metals (Pb) and Coliform bacteria in their bodies. This makes it dangerous to be consumed by humans. Thus, this research has two main aims. First, to find out the concentration of Pb and Coliform inside Corbicula largillierti that lives at Kapuas river, Pontianak and the river’s water. Second, to analyze the health risk of consuming the clams. Furthermore, the Atomic Absorption Spectrophotometer (AAS) is used to analyze the Pb sample and the Most Probable Number (MPN) method is used to analyze the Coliform. The result of this research shows that concentration Pb and Coliform from the Kapuas river have exceeded the limits designated for aquatic biota based on the Decree of the State Minister for the Environment No. 51 of 2004. In addition, the health risk is measured using Estimated Daily Intake (EDI), Target Hazard Quotient (THQ) and Target Carcinogenic Risk (TR) with scores for each are >10 times the RfD, >1 and 10−3. This result shows that based on the clam Corbicula largillierti consumption for 70 years life span of 60 kg body weight,  had a high and negative effect on health risk problems and had a cancer risk for consumers. However, the health risk problem might increase much worse due to the long and continual period of consumption exceeding estimated daily intake.